A Synectic Approach to Listening Learning: Integrating Local Culture and Audiovisual Technology in Indonesian Language Education - Yuni Ertinawati; Maman Suryaman; Kastam Syamsi (ASEAN Journal of Educational Research and Technology, 2025)
This study aims to develop a learning model for listening skills that integrates a synthetic approach, local cultural content, and audiovisual technology in Indonesian language education. Employing a Research and Development (R&D) design with the ADDIE framework (Analysis, Design, Development, Implementation, and Evaluation), data were collected through surveys, interviews, observations, and expert evaluations, and analyzed using both qualitative and quantitative methods. The findings indicate that integrating local cultural content with audiovisual technology not only enhances students’ listening skills but also increases their motivation and active participation. By presenting learning material that is culturally relevant, engaging, and interactive, students become more interested, involved, and motivated throughout the learning process. Further research is recommended to examine the feasibility of this model across diverse educational contexts and to develop more comprehensive assessment tools that can better capture improvements in listening skills and student engagement.